Interventions That Target Criminogenic Needs for Justice-Involved Persons With Serious Mental Illnesses: A Targeted Service Delivery Approach. (October 2018) - Wilson, Amy Blank; Farkas, Kathleen; Bonfine, Natalie; Duda-Banwar, Janelle
This research describes the development of a targeted service delivery approach that tailors the delivery of interventions that target criminogenic needs to the specific learning and treatment needs of justice-involved people with serious mental illnesses (SMI). This targeted service delivery approach includes five service delivery strategies: repetition and summarizing, amplification, coaching, low-demand practice, and maximizing participation. Examples of how to apply each strategy in session are provided, as well as recommendations on when to use each strategy during the delivery of interventions that target criminogenic needs. This targeted service delivery approach makes an important contribution to the development of interventions for justice-involved people with SMI by increasing the chances that people with SMI can participate fully in and benefit from these interventions that target criminogenic needs. These developments come at a critical time in the field as the next generation of services for justice-involved people with SMI are being developed.